On Generalized Carleson Operators of Periodic Wavelet Packet Expansions - Shyam Lal; Manoj Kumar (The Scientific World Journal)
Three new theorems based on the generalized Carleson operators for the periodic Walsh-type wavelet packets have been established. An application of these theorems as convergence a.e. for the periodic Walsh-type wavelet packet expansion of block function with the help of summation by arithmetic means has been studied.